Perspectiva global das viagens dos portugueses às Canárias no âmbito dos descobrimentos e expansão portuguesa : uma questão adiada até Alcaçovas-Toledo (1479-80) - Silva, Isabel L. Morgado de S. e (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Despite the questions that have always been associated with the issue of the Canary Islands, visible in the many studies done on them, it is not by any means inconvenient to revisit these islands – in a global perspective –, thus, confirming, once again, their importance in the process of the Portuguese discoveries and expansion.